Integration in Global Value Chains-the Role of Service Inputs Evidence from India - Manghnani, Ruchita (The World Bank, 2021)
This paper investigates the relationship between the use of service inputs and integration in global value chains. Using macro and detailed firm-level data (for 1990-2017), the study documents the extent of India's integration into global value chains. Older, larger, and more productive firms and firms with a higher leverage ratio are more likely to be deeply integrated into global value chains. Firms in the information technology services and electronics industry are more deeply integrated into global value chains, compared with textiles. Services are the engine for many global value chain industries as they help coordinate the different stages of production across geographical locations. The findings suggest that both the intensity of service usage as well as the composition or type of service used are important. Firms using service inputs, particularly complex services and information technology and information technology-enabling services intensively are typically more deeply integrated into global value chains